Protestant Textuality and the Tamil Modern Political Oratory and the Social Imaginary in South Asia - Bate, Bernard (South Asia in Motion, 2021)
Throughout history, speech and storytelling have united communities and mobilized movements. Protestant Textuality and the Tamil Modern examines this phenomenon in Tamil-speaking South India over the last three centuries, charting the development of political oratory and its influence on society. Supplementing his narrative with thorough archival work, Bernard Bate begins with Protestant missionaries' introduction of the sermonic genre and takes the reader through its local vernacularization. What originally began as a format of religious speech became an essential political infrastructure used to galvanize support for new social imaginaries, from Indian independence to Tamil nationalism. Completed by a team of Bate's colleagues, this ethnography marries linguistic anthropology to performance studies and political history, illuminating new geographies of belonging in the modern era.